Successful Administration of Recombinant Human Soluble Thrombomodulin α (Recomodulin) for Disseminated Intravascular Coagulation during Induction Chemotherapy in an Elderly Patient with Acute Monoblastic Leukemia Involving the t(9;11)(p22;q23) MLL/AF9 Translocation - Takagi, Kazutaka; Tasaki, Toshiki; Yamauchi, Takahiro; Iwasaki, Hiromichi; Ueda, Takanori (Case Reports in Hematology, 2011)
Patients with acute myelogenous leukemia complicate with disseminated intravascular coagulation (DIC), not only at the time of the initially leukemia diagnosis, but also during induction chemotherapy. In Japan, recently, a recombinant human soluble thrombomodulin alpha (Recomodulin) has been introduced as a new type of anti-DIC agent for clinical use in patients with hematological cancer or infectious disease. We describe a 67-year-old female case in which 25,600 units of Recomodulin for 6 days were successfully administered for both initially complicating and therapy-induced DIC without any troubles of bleeding in an acute monoblastic leukemia (AML-M5a) patient with the MLL gene translocation. Furthermore, the levels of DIC biomarkers recovered rapidly after the Recomodulin treatment. Our case suggests that DIC control using Recomodulin is one of the crucial support-therapies during remission induction chemotherapy in patients with acute leukemia of which type tends to complicate extramedullary or extranodal infiltration having potential to onset DIC.